Társadalmi vállalkozások gasztronómiai lehetőségei a rövid élelmiszerellátási láncok bevonásával Magyarországon - Török, Áron; Agárdi, Irma (Vezetéstudomány / Budapest Management Review, 2020)
The study aims to assess the long term economical sustainability of the social enterprises doing their businesses in the catering sector. Based on the findings of investigating three prominent members of the Hungarian para-gastro movement we can conclude that these enterprises have to face with all the difficulties of the industry, and their special circumstances might make their operations even more difficult. Considering the support (e.g.: several subsidies, reductions) received in order to reach their social goals, the opportunities provided by the short food supply chains can help them only in case they find a niche market where solvent demand can accept the specialties of local sourcing.